2013
DOI: 10.1186/1471-2334-13-462
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for diseases attributable to human papillomavirus in the Veneto Region (North-East Italy)

Abstract: BackgroundHuman papillomavirus (HPV) is one of the most common sexually-transmitted pathogens. A number of studies in the literature have estimated the burden of HPV-related diseases by collecting data at primary care level, while a comprehensive assessment of the global burden of HPV-related diseases on hospital resources is still lacking.MethodsThis was a retrospective cohort study based on hospital discharge data collected from 2000 to 2010 in the Veneto Region (north-east Italy). All hospitalizations for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…A previous work on HPV-related hospitalization in the same geographical area showed that hospital admissions for GWs increased in both genders from 2000 to 2010, pointing to the need for prevention programs [16]. The data emerging from the present study show a reversal of the trend of hospital admissions for the treatment of GWs, a number of factors might explain this picture besides the increase in HPV vaccination coverage rate.…”
Section: Discussionsupporting
confidence: 57%
“…A previous work on HPV-related hospitalization in the same geographical area showed that hospital admissions for GWs increased in both genders from 2000 to 2010, pointing to the need for prevention programs [16]. The data emerging from the present study show a reversal of the trend of hospital admissions for the treatment of GWs, a number of factors might explain this picture besides the increase in HPV vaccination coverage rate.…”
Section: Discussionsupporting
confidence: 57%
“…Hence, strength of the study is constituted by the size of the population analysed especially if we consider that data are representative of all hospitals in Veneto and Marche territory. By doing so, this work represents an evolution of the previous study conducted only in Veneto [3]. Overall, the hospitalization rates of the two regions were comparable: 49.44 hospitalizations in Veneto and 48.41 in Marche per 100,000 individuals.…”
Section: Discussionmentioning
confidence: 64%
“…This study represents a first attempt to quantify the hospitalization rates of HPV-related diseases [3], as well as a measure of the economic burden of these hospitalizations from the Italian National Health Service perspective. At the time of the analysis, the population over 18 years old amounted to over €5,3 million, €4 million in Veneto and €1,3 in Marche that was almost 9% of the total Italian population [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations